Improving the catalytic behaviors of Lactobacillus-derived fructansucrases by truncation strategies - TOKSOY ÖNER, EBRU (ELSEVIER SCIENCE INC, 2021)
Fructansucrases (FSs), including inulosucrase (IS) and levansucrase (LS), are the members of the Glycoside Hydrolase family 68 (GH68) enzymes. IS and LS catalyze the polymerization of the fructosyl moiety from sucrose to inulin- and levan-type fructans, respectively. Lactobacillus-derived FSs have relatively extended N- and Cterminal sequences. However, the functional roles of these sequences in their enzymatic properties and fructan biosynthesis remain largely unknown. Limosilactobacillus reuteri (basionym: Lactobacillus reuteri) 121 could produce both IS and LS, abbreviated as Lare121-IS and Lare121-LS, respectively. In this study, it was found that the terminal truncation displayed an obvious effect on their activities and the N-terminal truncated variants, Lare121-IS Delta 177-701 and Lare121-LS Delta 154-686, displayed the highest activities. Melting temperature (Tm) and the thermostability at 50 degrees C were measured to evaluate the stability of various truncated versions, revealing the different effects of N-terminal on the stability. The average molecular weight and polymerization degree of the fructans produced by different truncated variants did not change considerably, indicating that N-terminal truncation had low influence on fructan biosynthesis. In addition, it was found that N-terminal truncation could also improve the activity of other reported FSs from Lactobacillus species.
Keywords: Inulosucrase; Levansucrase; Lactobacillus reuteri; Terminal truncation; CRYSTAL-STRUCTURE; MOLECULAR CHARACTERIZATION; LEUCONOSTOC-CITREUM; INULOSUCRASE; LEVANSUCRASE; INULIN; REUTERI; FRUCTOSYLTRANSFERASE; AMYLOPULLULANASE; BIOSYNTHESIS